Strategi Keberlanjutan Inovasi Daerah di Kota Bandung - Wardani, Dyah Kusuma; Apriani, Tini (Research and Development Agency Ministry of Home Affairs, 2023)
A large number of regions compete for regional innovation. However, in fact, many of them are trapped in a collection of innovations without thinking about the sustainability of the regional innovations it self. This study aims to provide an overview of how the City of Bandung can continue to find new innovations without ignoring the innovations that have existed before. The study was conducted with a qualitative approach, where data were obtained through interviews and literature searches. The results of the study show that the sustainability of innovation in an area can be done not only by creating a new innovation that has never been implemented in the area, but can be done by updating or developing innovations that have been applied before. The results of this study can be a consideration for other regions when designing innovations. Â Therefore, innovations are not only made for assessment but also for sustainability and beneficial to society.